Incarcerated Amyand hernia: a rare entity - Rai, Vijeth; Siva, Ranadheer Raju Cholaraju; Deep, Gagan (International Surgery Journal, 2020)
Right sided inguinal hernia containing vermiform appendix in its sac is called as amyand’s hernia. It accounts for ∼1% of all inguinal hernias. It is an intra operative finding during an inguinal hernia repair. A 64 years old male patient came with complains of swelling in the right inguinal region, associated with pain and vomiting. On examination of the right inguinal region there was a tender irreducible swelling palpable. Based on the characteristic finding it was diagnosed clinically as right sided irreducible obstructed inguinal hernia. Ultrasound abdomen was done which was suggestive of right inguinal hernia with herniation of bowel and omentum with features of strangulated/ obstructed hernia. Patient was taken up for right inguinal hernia repair and appendix was noted in the hernial sac intra-operatively. Although occurrence of amyand’s hernia is rare. The attendant surgeon should be vigilant about the presence of it. Preoperative diagnosis of amyand’s hernia is not common because in majority of cases objective of imaging is to exclude conditions that predispose to inguinal hernia formation. The Losanoff and Basson’s criterion is used as a guide for deciding whether to perform appendectomy and type of repair, depend on the clinical scenario.